Description of the female of Aradus superstes Germar & Berendt, 1856 from the Eocene Baltic amber (Hemiptera: Aradidae) - Azar, Dany (Zootaxa, 2025)
Aradus superstes Germar & Berendt, 1856 from Eocene Baltic amber is known from a sole male specimen. Herein the female of this fossil species is described and illustrated.